Israeli peace discourse : a cultural approach to CDA - Gavriely-Nuri, Dalia (Discourse approaches to politics, society, and culture., 2015)
What role do language and discourse play in the advancement of peace? What is the connection between a given society's "peace language" and the repeated failure of peace initiatives involving it? At the heart of this book lie these basic questions and the attempt to shed light on them from new angles. The book focuses on an analysis of Israeli peace discourse and indicates the need for change in this discourse in order to promote a "culture of peace". It presents the process of peace-estrangement, a set of linguistic, discursive and cultural devices intended for creating doubt regarding the positive meaning associated with the concept of peace. The approach adopted in this book is the Cultural Approach to Critical Discourse Analysis (CCDA). This approach aims at exposing the cultural codes embedded in the discourse, which contribute to reproducing abuses of social power. The analytic chapters focus on different historical periods, since the beginning of the 20th century to this day, and deal with various genres found in diverse corpora, such as Knesset records and school textbooks